2017
DOI: 10.1002/cam4.1127
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR inhibition in concurrence with ERK1/2 activation is involved in excessive autophagy induced by glycyrrhizin in hepatocellular carcinoma

Abstract: Autophagy is a life phenomenon in which autophagosomes remove damaged or aging organelles and long‐lived circulating proteins to maintain the cell's stability. However, disorders of excessive autophagy are a response of cancer cells to a variety of anticancer treatments which lead to cancer cell death. The Akt/mammalian target of rapamycin (mTOR) and the extracellular signal‐regulated kinase 1/2 (ERK1/2) pathways are both involved in nutrient‐induced autophagic phenomenon and exhibit vital relevance to oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…Evidence has confirmed that RAD001 can substantially induce autophagy, as well as promote the apoptosis of breast cancer cells 22 and hepatocellular carcinoma cells. 23 , 24 Similarly, the results of the present experiment showed that RAD001 treatment of RCC cells resulted in the upregulation of LC3-II/I and downregulation of p62, which are typical features of autophagy induction, suggesting that autophagy by 786-O and A498 cells was induced by RAD001 treatment. So, high concentrations of RAD001 were used in this experiment due to the grade of the RCC cell lines 786-O and A498.…”
Section: Discussionsupporting
confidence: 74%
“…Evidence has confirmed that RAD001 can substantially induce autophagy, as well as promote the apoptosis of breast cancer cells 22 and hepatocellular carcinoma cells. 23 , 24 Similarly, the results of the present experiment showed that RAD001 treatment of RCC cells resulted in the upregulation of LC3-II/I and downregulation of p62, which are typical features of autophagy induction, suggesting that autophagy by 786-O and A498 cells was induced by RAD001 treatment. So, high concentrations of RAD001 were used in this experiment due to the grade of the RCC cell lines 786-O and A498.…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies have shown that multiple anticancer treatments result in the disorders of excessive autophagy and further lead to cancer cell death [14,15]. The Akt/mTOR pathway is suggested to play a key role in nutrient‐induced autophagy and is tightly correlated with oncogenesis in different cancer cells [16]. However, whether MA could induce autophagic death through this pathway in thyroid cancer cells has never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Among recent reports on the antitumor potential of glycyrrhizin (8), its cytotoxicity toward HepG2 and MHCC97-H hepatocellular carcinoma cells was found to be mediated by autophagy induced from the inhibition of Aκt/mTOR signaling [47]. It is worth mentioning that Glycyrrhiza uralensis Fisch.…”
Section: Lupane-type Triterpenoidsmentioning
confidence: 99%